Pelatihan Pengolahan Singkong (Manihot Esculanta. L) Menjadi Brownies Telo Sebagai Upaya Meningkatkan Ekonomi Masyarakat) - Aep Kusnawan; Nurul Hidayah (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2022)
Cassava or what is known as telo is one of the main commodities produced by community plantations in Padukuhan Jetis, Jetis Saptosari. This food which has a very high carbohydrate content can be used as a substitute for rice. The purpose of this training activity is to provide on cassava processing innovation as an effort to increase the economic value of cassava. This cassava processing innovation training activity was held on 23 August 2022 at 13:00-16:00 WIB at the Padukuhan Jetis hall with the initial activity being filled with material socialization events about processed cassava innovation and continued with the practice of making steamed telo brownies with the participants. This activity is expected to be an innovation for the community to make more use of cassava into processed products that have high economic value.